STEM – EDUCATION AS ONE OF THE METHODS OF DIGITALIZATION OF VOCATIONAL EDUCATION (Innovative professional education, 2023)
In the conditions of the digital transformation of the educational process, there is a need to increase the level of digital competence of the participants of the educational process, which includes information and technical literacy, communication in a digital educational environment, cooperation, training and self-study. The rapid development of technologies requires professionals in any field, which is why STEAM education is now very relevant. This trend will continue in the future. Elements of STEAM education were introduced into the educational process of the vocational and technical institution, a theoretical study was conducted on the use of STEM technologies as a means of increasing digital competences among students. The practical significance of STEAM education for the formation of a permanent interest in studying natural and mathematical disciplines, mastering of technological literacy and problem solving skills, involvement in research, invention, and project activities has been proven.
Keywords: STEAM education, education seekers, digital competence, cognitive independence, method